Asphalt concrete wearing layer based on RAP material and construction method

By modifying RAP material and preparing a composite warm mix agent using a composite of polyester emulsion and bamboo fiber and nano-alumina, the adhesion and high and low temperature resistance of the wear layer of RAP material were solved, and the mechanical strength and deformation resistance were improved.

CN120841881APending Publication Date: 2025-10-28JIANGSU RIVENDELL TRANSPORTATION TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510942165.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-09
Publication Date
2025-10-28

AI Technical Summary

Technical Problem

Existing abrasion layer materials have high porosity, require high adhesion between asphalt and aggregates, and have poor high and low temperature resistance and mechanical strength.

Method used

RAP waste was modified using a composite of polyester emulsion and bamboo fiber, and a composite warm mix agent was prepared by combining it with nano-alumina. By improving the adhesion and porosity of RAP material, the high and low temperature resistance and mechanical strength of asphalt concrete were improved.

Benefits of technology

It improves the mechanical strength and high and low temperature resistance of RAP asphalt concrete wearing course, exhibiting higher shear strength and flexural strength.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses an asphalt concrete wearing layer based on an RAP material and a construction method, belongs to the technical field of building materials, and aims at solving the problems that in the prior art, a wearing layer material is large in porosity and high in requirement for adhesion of asphalt and aggregate; and the asphalt concrete wearing layer adopting the RAP material is poor in high and low temperature resistance and mechanical property. A construction method of an asphalt concrete wearing layer based on an RAP material comprises the following steps that coarse aggregate, fine aggregate, mineral powder, recycled RAP waste and a composite warm mixing agent are mixed, and a uniform mixture is obtained; the uniform mixture is subjected to paving, initial pressing, re-pressing and final pressing, and the asphalt concrete wearing layer of the RAP material is prepared. The prepared asphalt concrete wearing layer based on the RAP material has the characteristics of excellent high and low temperature resistance, excellent mechanical strength such as shear strength and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of building materials technology, specifically to an asphalt concrete wearing course based on RAP material and its construction method. Background Technology

[0002] RAP (Recycled Asphalt Mixture) is a mixture of asphalt pavement that has been excavated, recycled, crushed, and screened, and then remixed with new aggregates in a certain proportion. With the increasing mileage of highways in my country, especially expressways, many early-built highways have entered the renovation and maintenance stage before reaching their service life, making the disposal of old asphalt pavement material obtained from the milling of old roads a difficult problem.

[0003] Wear course technology is a common road maintenance technique. As the surface layer in direct contact with tires, it is easily affected by factors such as climate, load, and service life, leading to a decline in performance. Traditional wear courses have disadvantages such as large thickness, high energy consumption, and serious environmental pollution problems. If RAP (Rapid Adhesive Packing) material can be recycled and used to prepare wear course materials, resource reuse can be achieved. However, wear course materials have high porosity, which places higher demands on the adhesion between asphalt and aggregates. In addition, compared with virgin asphalt, RAP material suffers from reduced resistance to high and low temperatures and mechanical properties. Maintaining the high and low temperature resistance and mechanical strength of asphalt concrete wear courses using RAP material is also a technical problem that urgently needs to be solved.

[0004] To address this technical deficiency, a solution is proposed. Summary of the Invention

[0005] The purpose of this invention is to provide an asphalt concrete wearing course based on RAP material and a construction method thereof, in order to solve the technical problems of high porosity of wearing course materials, high requirements for the adhesion between asphalt and aggregates, and poor high and low temperature resistance and mechanical strength of asphalt concrete wearing courses using RAP material in the prior art.

[0006] The purpose of the present invention can be achieved through the following technical solutions: A construction method for an asphalt concrete wearing course based on RAP material includes the following steps: S1. According to the weight, mix 30-40 parts of coarse aggregate, 20-30 parts of fine aggregate, 5-15 parts of mineral powder, 10-20 parts of recycled RAP waste, and 0.2-0.5 parts of composite warm mixing agent to obtain a uniform mixture. S2. The uniform mixture is spread, initially compacted, then compacted again and finally compacted to prepare the asphalt concrete wearing course of RAP material.

[0007] Further, in step S1, the method for preparing the recycled RAP waste includes the following steps: A1. RAP waste is heated at 95-105℃ for 2-3 hours to obtain softened RAP waste; the softened RAP waste is mixed with solvent to obtain mixed waste material; the mixed waste material is centrifuged and dried to evaporate the solvent to obtain recycled material; A2. A slurry preparation tank, an esterification reactor, and a polycondensation reactor are connected to form a batch reactor. Ethylene glycol, lysine diisocyanate, terephthalic acid, and a catalyst are added to the slurry preparation tank to obtain a prepared slurry. The esterification reactor is placed under a nitrogen atmosphere, and the prepared slurry is then added to the esterification reactor. The pressure of the esterification reactor is set to 0.1-0.4 MPa, the temperature of the esterification reactor is set to 245-265℃, and the esterification reaction time is set to 2.5-3.5 h to synthesize the esterification product. A3. The esterification product is transferred to the polycondensation reactor. The pressure of the polycondensation reactor is 100-200 Pa. The temperature of the polycondensation reaction is set to 270-295℃ and the duration of the polycondensation reaction is 3-5 h. The product obtained is the synthesized polyester emulsion. Polyester emulsions were synthesized via polymerization using terephthalic acid, ethylene glycol, and lysine diisocyanate as raw material monomers and antimony glycolate as a catalyst.

[0008] A4. Polyester emulsion and bamboo fiber are blended to obtain a composite; the composite is mixed with recycled material and stirred at high speed to prepare recycled RAP waste.

[0009] Further, in step A1, the mass ratio of softened RAP waste to solvent is 1:2-3; the centrifugation speed is 2000-3000 r / min and the centrifugation time is 15-30 min; the drying temperature is 90-95℃.

[0010] Further, in step A2, the ratio of ethylene glycol, lysine diisocyanate, terephthalic acid, and catalyst is 30-50 mL: 10-20 g: 16-32 g: 0.3-0.5 g; in step A4, the mass ratio of polyester emulsion to bamboo fiber is 1:3-5, and the mass ratio of composite to recycled material is 1:10-20; the high-speed stirring speed is 2000-3000 r / min, and the high-speed stirring time is 20-30 min.

[0011] Furthermore, the preparation method of the composite warm-mix agent includes the following steps: Sodium dodecylbenzenesulfonate powder was added to deionized water and stirred until the sodium dodecylbenzenesulfonate powder was completely dissolved to obtain an aqueous surfactant solution. Based on a solid-liquid ratio of 1-2:5, nano-alumina was immersed in the aqueous surfactant solution for 2-3 hours at a temperature of 50-60°C. After filtration and vacuum drying, a composite warm mixing agent was prepared.

[0012] Furthermore, the ratio of sodium dodecylbenzenesulfonate powder to deionized water is 15-20g:100mL; the vacuum drying temperature is 70-80℃ and the vacuum drying time is 20-30min.

[0013] Furthermore, in step S1, the mixing time is 45-60s and the mixing temperature is 160-170℃; in step S2, the paving thickness is 25-35mm.

[0014] As another aspect of the present invention, a construction method for an asphalt concrete wearing course based on RAP material yields an asphalt concrete wearing course based on RAP material.

[0015] The present invention has the following beneficial effects: 1. After centrifugation, the asphalt and fine aggregates in the RAP waste can be effectively separated, thus obtaining recycled material. To improve the viscosity of the recycled material with the remaining components of the asphalt concrete wearing course, this invention uses a composite of polyester emulsion and bamboo fiber to modify the recycled material. The polyester emulsion uses terephthalic acid and ethylene glycol as raw material monomers and is modified with lysine diisocyanate to increase the content of polar functional groups in the polyester emulsion and improve its adhesion. This results in the asphalt concrete wearing course based on RAP waste prepared by this invention having high mechanical strength, specifically a high shear strength.

[0016] 2. This invention utilizes the large specific surface area of ​​nano-alumina to adsorb sodium dodecylbenzenesulfonate, thereby preparing a composite warm-mix agent. Asphalt concrete is modified using this composite warm-mix agent. By forming a lubricating film on the surface of the asphalt concrete and filling the asphalt concrete with nano-sized inorganic materials, the micropores in the asphalt concrete are filled, thereby improving the low-temperature and high-temperature resistance of the prepared asphalt concrete. Detailed Implementation

[0017] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0018] The RAP waste used in Examples 1-3 of this invention was milled material from an asphalt pavement section in Anhui that had been in service for five years; the bamboo fiber used in Examples 1-3 of this invention was purchased from Changzhou Le'en Biotechnology Co., Ltd., with a particle size of 200-300 mesh; the nano-alumina used in Examples 4-6 of this invention was purchased from Shanghai Keliansheng New Materials Co., Ltd., model KLS-AlO3-K10, with an average particle size of 10nm and a specific surface area of ​​210m².2 / g; The basalt used in Examples 4-6 of this invention was purchased from Lingshou County Shengxiang Mineral Products Co., Ltd., with a particle size of 3-5mm; The natural sand used in Examples 4-6 of this invention was purchased from Lingshou County Zhanrui Mineral Products Processing Plant, with a particle size of 1.5-2.5mm; The limestone used in Examples 4-6 of this invention was purchased from Taixing City Yexin Building Materials Co., Ltd.

[0019] Example 1 This embodiment provides a method for preparing recycled RAP waste for asphalt concrete wearing courses based on RAP materials, including the following steps: A1. Heat the RAP waste at 95℃ for 2 hours to obtain softened RAP waste. Mix the softened RAP waste and the solvent trichloroethylene at a solid-liquid mass ratio of 1:2 to obtain mixed waste material. Pour the mixed waste material into a centrifuge and centrifuge at 2000 r / min for 15 min. Then dry it at 90℃ to evaporate the solvent trichloroethylene and obtain the recovered material.

[0020] A2. A batch reactor is formed by connecting a 500mL laboratory slurry preparation tank, a 500mL laboratory esterification reactor, and a 500mL laboratory polycondensation reactor. In the slurry preparation tank, 30mL of ethylene glycol, 10g of lysine diisocyanate, 16g of terephthalic acid, and 0.3g of antimony glycolate catalyst are added and mixed thoroughly to obtain a prepared slurry. The air in the esterification reactor is completely replaced with nitrogen. The prepared slurry is then fed into the esterification reactor, which is set to a pressure of 0.1MPa, a temperature of 245℃, and a reaction time of 2.5h to synthesize the esterification product.

[0021] A3. The esterification product is transferred to the polycondensation reactor, and a steam jet pump is used to evacuate the polycondensation reactor to a pressure of 100 Pa. The polycondensation reaction temperature is set to 270℃ and the reaction time is set to 3 hours to obtain the product. At this point, the intrinsic viscosity of the product is measured to be 0.5 dL / g, which is considered the end of the esterification reaction, and a polyester emulsion is synthesized.

[0022] A4. Polyester emulsion and bamboo fiber are blended at a mass ratio of 1:3 to obtain a composite. The composite and recycled material are added to a high-speed mixer at a mass ratio of 1:10. The high-speed mixer is operated at a speed of 2000 r / min for 20 min until homogeneous, thus preparing recycled RAP waste.

[0023] Example 2 This embodiment provides a method for preparing recycled RAP waste for asphalt concrete wearing courses based on RAP materials, including the following steps: A1. RAP waste is heated at 100℃ for 2.5 hours to obtain softened RAP waste. The softened RAP waste and solvent trichloroethylene are mixed at a solid-liquid mass ratio of 1:3 to obtain mixed waste material. The mixed waste material is poured into a centrifuge and centrifuged at 2500 r / min for 25 min. Then it is dried at 92℃ to evaporate the solvent trichloroethylene and obtain the recovered material.

[0024] A2. A 500mL laboratory slurry preparation tank, a 500mL laboratory esterification reactor, and a 500mL laboratory polycondensation reactor are connected to form a batch reactor. In the slurry preparation tank, 40mL of ethylene glycol, 15g of lysine diisocyanate, 28g of terephthalic acid, and 0.4g of antimony glycolate are added and mixed thoroughly to obtain a prepared slurry. The air in the esterification reactor is completely replaced with nitrogen. The prepared slurry is then fed into the esterification reactor, which is set to a pressure of 0.3MPa and a temperature of 260℃ to synthesize the esterification product.

[0025] A3. The esterification product is transferred to the polycondensation reactor. The polycondensation reactor is evacuated using a steam jet pump, and the pressure of the polycondensation reactor is 150 Pa. The polycondensation reaction temperature is set to 285℃ and the polycondensation reaction time is set to 5 h to obtain the product. At this time, when the intrinsic viscosity of the product is 0.55 dL / g, the esterification reaction is considered to be completed, and the polyester emulsion is synthesized.

[0026] A4. Polyester emulsion and bamboo fiber are blended at a mass ratio of 1:4 to obtain a composite. The composite and recycled material are added to a high-speed mixer at a mass ratio of 1:15. The high-speed mixer is operated at a speed of 2500 r / min for 25 min until homogeneous, thus preparing recycled RAP waste.

[0027] Example 3 This embodiment provides a method for preparing recycled RAP waste for asphalt concrete wearing courses based on RAP materials, including the following steps: A1. Heat the RAP waste at 105℃ for 3 hours to obtain softened RAP waste. Mix the softened RAP waste and the solvent trichloroethylene at a solid-liquid mass ratio of 1:3 to obtain mixed waste material. Pour the mixed waste material into a centrifuge and centrifuge at 3000 r / min for 30 min. Then dry it at 95℃ to evaporate the solvent trichloroethylene and obtain the recovered material.

[0028] A2. A 500mL laboratory slurry preparation tank, a 500mL laboratory esterification reactor, and a 500mL laboratory polycondensation reactor are connected to form a batch reactor. In the slurry preparation tank, 50mL of ethylene glycol, 20g of lysine diisocyanate, 32g of terephthalic acid, and 0.5g of antimony glycolate are added and mixed thoroughly to obtain a prepared slurry. The air in the esterification reactor is completely replaced with nitrogen. The prepared slurry is then fed into the esterification reactor, which is set to a pressure of 0.4MPa and a temperature of 265℃ to synthesize the esterification product.

[0029] A3. The esterification product is transferred to the polycondensation reactor. A steam jet pump is used to evacuate the polycondensation reactor, and the pressure of the polycondensation reactor is 200 Pa. The temperature of the polycondensation reaction is set to 295℃ and the duration of the polycondensation reaction is set to 5 hours to obtain the product. At this time, when the intrinsic viscosity of the product is 0.55 dL / g, the esterification reaction is considered to be completed, and the polyester emulsion is synthesized.

[0030] A4. Polyester emulsion and bamboo fiber are blended at a mass ratio of 1:5 to obtain modified bamboo fiber. The modified bamboo fiber and recycled material are added to a high-speed mixer at a mass ratio of 1:20. The high-speed mixer is operated at a speed of 3000 r / min for 30 min until uniform mixing is achieved, thus preparing recycled RAP waste.

[0031] Example 4 This embodiment provides a construction method for an asphalt concrete wearing course based on RAP material, including the following steps: S1. Add 15g of sodium dodecylbenzenesulfonate powder to 100mL of deionized water and stir until the sodium dodecylbenzenesulfonate powder is completely dissolved to obtain an aqueous surfactant solution. According to the solid-liquid ratio of 1:5, immerse nano alumina in the aqueous surfactant solution for 2 hours at an immersion temperature of 50℃, then filter and vacuum dry at 70℃ for 20 minutes to prepare a composite warm mixing agent.

[0032] S2. By weight, 30 parts of coarse aggregate basalt, 20 parts of fine aggregate natural sand, 5 parts of mineral powder limestone, 10 parts of recycled RAP waste prepared in Example 1, and 0.2 parts of composite warm mix agent are added to the asphalt mixture mixer. The mixing time is 45s and the mixing temperature is 160℃ to obtain a uniform mixture.

[0033] S3. The uniform mixture is spread on the construction road surface with a thickness of 35mm; then it is rolled three times with a road roller, namely initial rolling, intermediate rolling and final rolling, to finally prepare the asphalt concrete wearing course.

[0034] Example 5 This embodiment provides a construction method for an asphalt concrete wearing course based on RAP material, including the following steps: S1. Add 18g of sodium dodecylbenzenesulfonate powder to 100mL of deionized water and stir until the sodium dodecylbenzenesulfonate powder is completely dissolved to obtain an aqueous surfactant solution. Immerse nano-alumina into the aqueous surfactant solution at a solid-liquid ratio of 2:5, filter, and vacuum dry at 75℃ for 26min to prepare a composite warm mixing agent.

[0035] S2. By weight, 33 parts of coarse aggregate basalt, 25 parts of fine aggregate natural sand, 10 parts of mineral powder limestone, 15 parts of recycled RAP waste prepared in Example 2, and 0.3 parts of composite warm mix agent are added to the asphalt mixture mixer. The mixing time is 55s and the mixing temperature is 165℃ to obtain a uniform mixture.

[0036] S3. The uniform mixture is spread on the construction road surface with a thickness of 30mm; then it is rolled three times with a road roller, namely initial rolling, intermediate rolling and final rolling, to finally prepare the asphalt concrete wearing course.

[0037] Example 6 This embodiment provides a construction method for an asphalt concrete wearing course based on RAP material, including the following steps: S1. Add 20g of sodium dodecylbenzenesulfonate powder to 100mL of deionized water and stir until the sodium dodecylbenzenesulfonate powder is completely dissolved to obtain an aqueous surfactant solution. Immerse nano-alumina into the aqueous surfactant solution at a solid-liquid ratio of 2:5, then filter and vacuum dry at 80℃ for 30min to prepare a composite warm mixing agent.

[0038] S2. By weight, 40 parts of coarse basalt aggregate, 30 parts of fine natural sand aggregate, 15 parts of mineral powder limestone, 20 parts of recycled RAP waste prepared in Example 3, and 0.5 parts of composite warm mix agent were added to an asphalt mixing plant. The mixing time was 60 seconds and the mixing temperature was 170°C to obtain a homogeneous mixture. S3. The homogeneous mixture was spread on the construction road surface to a thickness of 25 mm. Then, it was compacted three times with a road roller, namely, initial compaction, intermediate compaction, and final compaction, to finally prepare an asphalt concrete wearing course based on RAP material.

[0039] Comparative Example 1 The difference between this comparative example and Example 6 is that step A1 is omitted when preparing recycled RAP waste, the RAP waste is not pretreated, and the recycled material is replaced with an equal mass of RAP waste.

[0040] Comparative Example 2 The difference between this comparative example and Example 6 lies in the method used to prepare the esterification product when preparing the recycled RAP waste. Specifically, it includes the following steps: A batch reactor was formed by connecting a 500mL laboratory slurry preparation tank, a 500mL laboratory esterification reactor, and a 500mL laboratory polycondensation reactor. In the slurry preparation tank, 70g of ethylene glycol, 32g of terephthalic acid, and 0.5g of antimony glycolate were added and mixed thoroughly to obtain a prepared slurry. The air in the esterification reactor was completely replaced with nitrogen, and then the prepared slurry was fed into the esterification reactor. The pressure of the esterification reactor was set to 0.4MPa, and the temperature was set to 265℃ to synthesize the esterification product.

[0041] Comparative Example 3 The difference between this comparative example and Example 6 is that 20g of sodium dodecylbenzenesulfonate powder was used instead of the prepared composite warm-mixing agent.

[0042] Performance testing: 1. According to JTGE20-2011 "Test Procedures for Asphalt and Asphalt Mixtures in Highway Engineering", rutting tests were conducted on the asphalt concrete wearing layers based on RAP waste prepared in Examples 4-6 and Comparative Examples 1-3 in sequence using a rutting tester.

[0043] 2. According to T0715-2011 "Bending Test of Asphalt Mixtures", low-temperature performance tests were conducted on the asphalt concrete wearing courses based on RAP waste prepared in Examples 4-6 and Comparative Examples 1-3 using an electronic universal testing machine. The test temperature was -10℃, and the loading rate was 50mm / min. The bending strength values ​​were recorded.

[0044] 3. Oblique shear tests were conducted sequentially on the specimens (asphalt concrete wearing courses based on RAP waste) prepared in Examples 4-6 and Comparative Examples 1-3 using an electronic universal testing machine. The oblique shear tester angle was 45°, the loading rate was 50 mm / min, and the tests were conducted at room temperature. The time from removing the specimen from the constant temperature oven to the specimen failing under load should not exceed 30 seconds.

[0045] Table 1. Sample performance test data

[0046] Data Analysis: By comparing and analyzing the data in Table 1, the asphalt concrete wearing courses based on RAP material prepared in Examples 4-6 of this invention all exhibit good rutting resistance under high-temperature conditions and high dynamic stability (mean DS value). The asphalt concrete wearing courses based on RAP material prepared in Examples 4-6 of this invention all exhibit good flexural performance under low-temperature conditions, demonstrating high flexural strength. However, in Comparative Example 1, the same mass of RAP waste was used to replace recycled material; the RAP waste was not centrifuged, and the asphalt and fine aggregates were not effectively separated. This resulted in the polyester emulsion failing to fully encapsulate the components of the recycled material, leading to reduced low-temperature and high-temperature resistance, as well as mechanical strength (flexural strength and shear strength) of the prepared asphalt concrete wearing courses.

[0047] In Comparative Example 2, the esterified product was not modified with lysine diisocyanate rich in various polar functional groups. The encapsulation and adhesion of the esterified product to the recycled material decreased, which was reflected in the reduced flexural strength and shear strength of the prepared RAP-based asphalt concrete wear layer.

[0048] In Comparative Example 3, no nano-alumina was added when preparing the warm mix agent. Nano-alumina has a large specific surface area, which can adsorb and recover polyester emulsion in RAP waste, thereby improving its mechanical strength. This is reflected in the reduced shear strength of the asphalt concrete prepared in Comparative Example 3.

[0049] The above description is merely an example and illustration of the structure of the present invention. Those skilled in the art can make various modifications or additions to the specific embodiments described, or use similar methods to replace them, as long as they do not deviate from the structure of the invention or exceed the scope defined in the claims, all of which should fall within the protection scope of the present invention.

[0050] In the description of this specification, references to terms such as "an embodiment," "example," and "specific example" indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the invention. In this specification, illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.

[0051] The preferred embodiments of the present invention disclosed above are intended only to help illustrate the present invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the present invention to specific embodiments. Obviously, many modifications and variations are possible based on the contents of this specification. These embodiments are selected and described in detail in this specification to better explain the principles and practical applications of the present invention, thereby enabling those skilled in the art to better understand and utilize the present invention. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A construction method for an asphalt concrete wearing course based on RAP material, characterized in that, Includes the following steps: S1. According to the weight, mix 30-40 parts of coarse aggregate, 20-30 parts of fine aggregate, 5-15 parts of mineral powder, 10-20 parts of recycled RAP waste, and 0.2-0.5 parts of composite warm mixing agent to obtain a uniform mixture. S2. The uniform mixture is spread, initially compacted, then compacted again and finally compacted to prepare the asphalt concrete wearing course of RAP material.

2. The construction method of asphalt concrete wearing course based on RAP material according to claim 1, characterized in that, In step S1, the method for preparing the recycled RAP waste includes the following steps: A1. RAP waste is heated at 95-105℃ for 2-3 hours to obtain softened RAP waste; the softened RAP waste is mixed with solvent to obtain mixed waste material; the mixed waste material is centrifuged and dried to evaporate the solvent to obtain recycled material; A2. A slurry preparation tank, an esterification reactor, and a polycondensation reactor are connected to form a batch reactor. Ethylene glycol, lysine diisocyanate, terephthalic acid, and a catalyst are added to the slurry preparation tank to obtain a prepared slurry. The esterification reactor is placed under a nitrogen atmosphere, and the prepared slurry is then added to the esterification reactor. The pressure of the esterification reactor is set to 0.1-0.4 MPa, the temperature of the esterification reactor is set to 245-265℃, and the esterification reaction time is set to 2.5-3.5 h to synthesize the esterification product. A3. The esterification product is transferred to the polycondensation reactor. The pressure of the polycondensation reactor is 100-200 Pa. The temperature of the polycondensation reaction is set to 270-295℃ and the duration of the polycondensation reaction is 3-5 h. The product obtained is the synthesized polyester emulsion. A4. Polyester emulsion and bamboo fiber are blended to obtain a composite; the composite is mixed with recycled material and stirred at high speed to prepare recycled RAP waste.

3. The construction method of asphalt concrete wearing course based on RAP material according to claim 2, characterized in that, In step A1, the mass ratio of softened RAP waste to solvent is 1:2-3; the centrifugation speed is 2000-3000 r / min and the centrifugation time is 15-30 min; the drying temperature is 90-95℃.

4. The construction method of an asphalt concrete wearing course based on RAP material according to claim 2, characterized in that, In step A2, the ratio of ethylene glycol, lysine diisocyanate, terephthalic acid, and catalyst is 30-50 mL: 10-20 g: 16-32 g: 0.3-0.5 g; in step A4, the mass ratio of polyester emulsion to bamboo fiber is 1:3-5, and the mass ratio of composite to recycled material is 1:10-20; the high-speed stirring speed is 2000-3000 r / min, and the high-speed stirring time is 20-30 min.

5. The construction method of asphalt concrete wearing course based on RAP material according to claim 1, characterized in that, The preparation method of the composite warm-mixing agent includes the following steps: Sodium dodecylbenzenesulfonate powder was added to deionized water and stirred until the sodium dodecylbenzenesulfonate powder was completely dissolved to obtain an aqueous surfactant solution. Based on a solid-liquid ratio of 1-2:5, nano-alumina was immersed in the aqueous surfactant solution for 2-3 hours at a temperature of 50-60°C. After filtration and vacuum drying, a composite warm mixing agent was prepared.

6. The construction method of an asphalt concrete wearing course based on RAP material according to claim 5, characterized in that, The ratio of sodium dodecylbenzenesulfonate powder to deionized water is 15-20g:100mL; the vacuum drying temperature is 70-80℃ and the vacuum drying time is 20-30min.

7. The construction method of asphalt concrete wearing course based on RAP material according to claim 1, characterized in that, In step S1, the mixing time is 45-60s and the mixing temperature is 160-170℃; in step S2, the paving thickness is 25-35mm.

8. A wearing course for asphalt concrete based on RAP material, characterized in that, The asphalt concrete wearing course based on RAP material is obtained by the construction method described in any one of claims 1-7.